2016
DOI: 10.1021/jacs.6b05762
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis and Receptor Binding of Mannose-6-Phosphate (M6P)-Containing Glycoprotein Ligands Reveal Unusual Structural Requirements for M6P Receptor Recognition

Abstract: Mannose-6-phosphate (M6P)-terminated oligosaccharides are important signals for M6P-receptor-mediated targeting of newly synthesized hydrolases from Golgi to lysosomes, but the precise structural requirement for the M6P ligand–receptor recognition has not been fully understood due to the difficulties in obtaining homogeneous M6P-containing glycoproteins. We describe here a chemoenzymatic synthesis of homogeneous phosphoglycoproteins carrying natural M6P-containing N-glycans. The method includes the chemical sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 46 publications
0
51
0
Order By: Relevance
“…The mutant was capable of synthesizing asialo biantennary and complex triantennary core-fucosylated glycoforms of rituximab (intact antibody) in yields over 95%. Further applications, indicating the high potential of the method for the synthesis of pharmaceutical relevant compounds were the chemoenzymatic production of vaccine candidates [ 72 ]; the site-selective glycosylation of HIV-1 polypeptide antigen bearing two different glycans (yields up to 95%) [ 73 ]; the glycan remodeling of human erythropoietin (EPO) [ 74 ]; and the synthesis of mannose-6-phosphate-containing glycoproteins [ 75 ]. Tang et al impressively demonstrated a one-pot N -glycan remodeling of IgG proteins by combining the wild type ( wt ) Endo-M glycosidase with the synthase variant Endo-S D322S [ 76 ].…”
Section: Glycoside Syntheses Using Glycosynthase Methodsmentioning
confidence: 99%
“…The mutant was capable of synthesizing asialo biantennary and complex triantennary core-fucosylated glycoforms of rituximab (intact antibody) in yields over 95%. Further applications, indicating the high potential of the method for the synthesis of pharmaceutical relevant compounds were the chemoenzymatic production of vaccine candidates [ 72 ]; the site-selective glycosylation of HIV-1 polypeptide antigen bearing two different glycans (yields up to 95%) [ 73 ]; the glycan remodeling of human erythropoietin (EPO) [ 74 ]; and the synthesis of mannose-6-phosphate-containing glycoproteins [ 75 ]. Tang et al impressively demonstrated a one-pot N -glycan remodeling of IgG proteins by combining the wild type ( wt ) Endo-M glycosidase with the synthase variant Endo-S D322S [ 76 ].…”
Section: Glycoside Syntheses Using Glycosynthase Methodsmentioning
confidence: 99%
“…5e-f). Bidentate binding to two arms of a single oligosaccharide was ruled out due to previously reported findings by Yamaguchi et al who demonstrated that a cyclic glycopeptide had a more than 10-fold higher affinity for CI-MPR than a phosphoglycoprotein ligand harboring a single M6P-phosphoglycan and that linearization of the cyclic glycopeptide through reduction of the disulfide resulted in an ~20-fold loss in affinity 48 . However, inspection of the X-ray structure (PDB 1EI9) revealed that PPT1's three N-glycans were grouped in close proximity to each other and molecular dynamics simulations demonstrate the inherent flexibility of glycans (Fig 6b).…”
Section: Evidence For a Secondary Carbohydrate Binding Sitementioning
confidence: 99%
“…Although in later papers Shoda has published alternative reagents that may be used to achieve the same transformation, such as 2-chloro-1,3-dimethyl-1 H -benzimidazol-3-ium chloride (CDMBI) [ 43 ], DMC remains the most popular reagent for glycosyl oxazoline production. DMC is remarkably tolerant of other functional groups in the oligosaccharide, for example sialic acids [ 44 ] and phosphates [ 45 46 ] are completely unaffected; the former is perhaps rather surprising since DMC was first developed as a carboxylic acid activating agent for peptide synthesis by Ishikawa [ 47 ]! One caveat to the procedure is that it is considerably less efficient for GalNAc; in this case the corresponding oxazoline is only produced in ≈50% yield.…”
Section: Reviewmentioning
confidence: 99%